Early stage blockade of the alarmin HMGB1 reduces cartilage destruction in experimental OA. Issue 5 (May 2020) - Aulin, C.; Lassacher, T.; Palmblad, K.; Erlandsson Harris, H.
Summary: Objective: The alarmin HMGB1 is an endogenous molecule that is released into the extracellular space upon trauma or cell activation. Extracellular HMGB1 initiates innate immune responses and besides mediating inflammation, has osteoclast-activating features and mediates pain, all important features in OA. The aim of this study was to examine the involvement of HMGB1 in experimental OA and to explore the effect of local anti-HMGB1-therapy on disease progression. Method: OA was induced in mice by surgical destabilization of knee joints and HMGB1 expression and localization was assessed by immunohistochemistry. For therapy evaluation, HMGB1-neutralizing antibodies were injected intraarticularly, alone or encapsulated in an injectable hyaluronan-based delivery vehicle. Human primary chondrocytes were stimulated with rHMGB1 and analyzed by qPCR and cytometric bead-array. Results: HMGB1 immunostaining of mouse OA joints demonstrated intra- and pericellular expression in chondrocytes, overlapping with proteoglycan depleted areas. Intra-articular injection of anti-HMGB1 antibodies had cartilage-protective effects, comparable to treatment with a TNF inhibitor. Direct and vehicle-based delivery had similar ameliorating effects and the effect of a single, early injection could not be enhanced by repeated injections. In vitro stimulation of chondrocytes with rHMGB1 affected chondrocyte function by inducing protein expression of IL6 and IL8 and downregulating mRNA of COL2A1. Conclusions: Our results suggest that the alarmin HMGB1 might be a new target for OA therapy development as we could observe an aberrant HMGB1 expression in mouse OA joints, stimulation of chondrocytes with rHMGB1 induced cytokine production and decreased matrix production and finally that HMGB1 blockade suppressed disease progression.